PENGARUH SENAM KAKI PADA LANSIA PENDERITA DIABETES MELLITUS DI PUSKESMAS DUREN SAWIT - Desi Purnamasari (Jurnal Nurse, 2022)
Physical exercise is very important in controlling diabetes because of its effect on lowering blood glucose levels by increasing glucose uptake by muscles and improving insulin use. The purpose of the study was to determine the effect of foot exercise on the elderly with diabetes mellitus at the Duren Sawit Health Center. The research design used is a quasi-experimental where the subject group is observed before the intervention is carried out, then observed again after the intervention is carried out. From the results of this study, it can be seen that 78.4% of those who follow leg gymnastics are elderly people who are more than 60 years old and 64.9% are women. The statistical test results obtained p-value = 0.000, it can be concluded that there is a significant difference between before and after DM foot exercise on the sensitivity of the feet of elderly people with DM.